Nilpotent L-subgroups and the Set Product of L-subsets (European Journal of Pure and Applied Mathematics, 2017)
In this paper, we study the set product of a pair of nilpotent normal L-subgroups of a given L-group. A necessary mechanism is developed in order to establish this result. Moreover, the tail of L-subgroups is used effectively while developing this mechanism.
Keywords: L-algebra; L-subgroup; Generated L-subgroup; Normal L-subgroup; Nilpotent L-subgroup